Cronstedtite from Litosice, Czech Republic - Hybler,J.; Dolnicek,Z.; Sejkora,J. (Journal of Geosciences, 2021)
The layered iron silicate cronstedtite was encountered in ore veins in the exploration shaft mined in the Neoproterozoic black shale-hosted pyrite-manganese deposit near Litosice (Eastern Bohemia, Czech Republic) around 1955. It forms up to 2 mm thick black double or single bands in symmetrically zoned hydrothermal veins cutting shales. The specimens selected from available material were studied by single-crystal X-ray diffraction using the four-circle diffractometer with an area detector. The chemical composition of some of the specimens was determined by the electron probe microanalysis (EPMA) in the WDS mode. Furthermore, a polished section of the ore material with cronstedtite bands was prepared, and the mineral association was analyzed with the aid of back-scattered electron (BSE) images. The interpretation of reciprocal space (RS) sections produced by the diffractometer software allowed the determination of OD subfamilies (Bailey’s groups) A, B, C, D, and polytypes. The 1T polytype (subfamily C), a = 5.52, c = 7.12 Å, space group P31m, is the most abundant in the occurrence. In rare cases, it forms oriented crystal associations (allotwins) with the 1M polytype (subfamily A), a = 5.52 Å, b = 9.55, c = 7.136 Å, β = 104.4°, space group Cm. Fully disordered allotwinned crystals of the A+C subfamilies were found, too. In addition, few allotwins of the polytype 2H1 (subfamily D) with a small amount of 2H2, were identified. Unit cell parameters are a = 5.49, c = 14.21 Å, space groups are P63cm (2H1), and P63 (2H2). EPMA-WDS of selected crystals of prevailing 1T polytype revealed elevated contents of Mn (0.19-0.62 apfu) and low contents of Mg (up to 0.13 apfu) and Cl (up to 0.05 apfu), respectively. More rare 2H1 (+2H2) polytypes show elevated contents of Mg in the range of 0.19-0.62 apfu and distinctly lower Mn (up to 0.07 apfu) and Cl contents (up to 0.01 apfu). The BSE images reveal that cronstedtite bands are associated with multiple generations of carbonates (rhodochrosite, siderite, rarely magnesite and calcite), quartz, opal, pyrite and carbonate-fluorapatite. Intense metasomatic replacement of cronstedtite by opal and siderite appeared especially around the center of the studied vein.
Keywords: Cronstedtite; 1 : 1 layered silicate; polytypism; stacking disorder; allotwinning